2006
DOI: 10.4049/jimmunol.177.3.1451
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Disease in New Zealand Black/New Zealand White Lupus-Prone Mice by Adoptive Transfer of Ex Vivo Expanded Regulatory T Cells

Abstract: An increasing number of studies indicate that a subset of CD4+ T cells with regulatory capacity (regulatory T cells; Tregs) can function to control organ-specific autoimmune disease. To determine whether abnormalities of thymic-derived Tregs play a role in systemic lupus erythematosus, we evaluated Treg prevalence and function in (New Zealand Black × New Zealand White)F1 (B/W) lupus-prone mice. To explore the potential of Tregs to suppress disease, we evaluated the effect of adoptive transfer of purified, ex v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
184
2
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(195 citation statements)
references
References 29 publications
6
184
2
3
Order By: Relevance
“…In a recent study by Scalapino and colleagues, it was demonstrated that the peripheral Treg frequency in the NZB/W F1 lupus strain of mice was reduced at a young age (8-10 wk). In contrast, in the aged diseased mice (48-52 wk), Treg frequency was found to be significantly increased in the renal draining lymph nodes while it was decreased in the spleen as compared to normal BALB/c mice [45]. The disparity in findings from the present study may reflect differences in the kinetics of disease progression, in relation to the age-dependent Treg changes, between the MRL/lpr and NZB/W strains.…”
Section: Discussioncontrasting
confidence: 89%
“…In a recent study by Scalapino and colleagues, it was demonstrated that the peripheral Treg frequency in the NZB/W F1 lupus strain of mice was reduced at a young age (8-10 wk). In contrast, in the aged diseased mice (48-52 wk), Treg frequency was found to be significantly increased in the renal draining lymph nodes while it was decreased in the spleen as compared to normal BALB/c mice [45]. The disparity in findings from the present study may reflect differences in the kinetics of disease progression, in relation to the age-dependent Treg changes, between the MRL/lpr and NZB/W strains.…”
Section: Discussioncontrasting
confidence: 89%
“…We have previously reported that older B6.NZBc13 mice exhibit almost half the proportion of Tregs than age-matched B6 mice [5]. As exogenous transfer of Tregs has been shown to delay disease progression and autoantibody production in lupus prone NZB/W F1 mice, Tregs derived from B6 BM cells may be responsible for the regulation of T-cell tolerance and antibody production seen in B6.NZBc13 MC mice [33,34]. Alternatively, the identification of an apoptotic debris clearance defect on NZB c13 suggests that the failure to effectively clear apoptotic debris contributes to the breach of tolerance in these mice.…”
mentioning
confidence: 97%
“…Interestingly, in a similar study, it was demonstrated that peripheral Treg frequency in the NZB/W F1 strain of mice, another spontaneous lupus mouse model, was rather reduced at young age. In contrast, in the aged and diseased mice, a higher Treg frequency was detected in the renal draining lymph nodes, though also decreased in the spleen, as compared to normal BALB/c mice [50]. This may again reflect the differences in severity and kinetics of disease progression, in relation to the age-dependent Treg cell changes, between the MRL/lpr and NZB/W F1 strains.…”
Section: Treg Deficiency In Systemic Autoimmunity -The Mutually Causamentioning
confidence: 87%
“…Instead, some of these studies suggested that Treg were functionally defective and less capable of suppressing those potentially auto-reactive lymphocytes in lupus patients [44,48,53,57,59,60,66,76,80], and the mouse models [70,89,90]. Again, alternative findings demonstrating lupus Treg being functionally normal [49,50,62,67,85], or at least normal in majority of patients tested [48,64], or even enhanced in some way [68,80,87] added further confusion as well as interest to the matter. Upon a closer examination, these seemingly discrepant findings can in fact be logically explained.…”
Section: Aberrant Treg Frequencies and Functions Associated With Lupumentioning
confidence: 99%